The pre-primary early childhood care and education (EECE) programme in Botswana: understanding its accessibility and quality - Pillar, Lebogang Joan (Graduate School of Development Policy and Practice, 2022)
Over the past few years, there has been rising interest in the field of Early Childhood Care and Education (ECCE). The interest is evident at international, regional and national levels. Given the widely documented benefits of ECCE, and through the lobbying of various stakeholders, the government of Botswana resolved to provide a one-year pre-primary programme at all government schools. In this study, ECCE and pre-primary education programme are used interchangeably. This pre-primary education programme was initially piloted at a few select schools in 2012. After the successful run of the programme, it was then scaled-up to all government primary schools in Botswana starting in 2014. This programme is the basis of this study, in which the researcher examines two of its main indicators namely accessibility and quality. The study was conducted using a qualitative research approach. It used the following research methods: document analysis, observation and structured and in-depth interviews with teachers, school heads and education officers from the Ministry of Basic Education (MoBE), the Department of Curriculum Development Evaluation (DCDE) and the Regional Education Office (REO). Twelve (12) schools were chosen out of a total of twenty – four 24 schools in the Gaborone sub-region. The data collected from the interviews and observations was analysed using thematic analysis. It was triangulated with the data obtained from documents. The study made three (3) key findings. First the study reveals that although the government achieved 86% scale-up rate of the programme, the student enrolment rate remains low, at an estimated 25%. Second the study also reveals inconsistency in resource allocation, in-service training of teachers and general support offered to the teachers and the schools among the studied schools. Finally, the study reveals that there is no quality framework, that the teachers improvise by using the expected learning outcomes contained in the Integrated Early Childhood Development (IECD) curriculum of 2013. Informed by the Lev Vygotsky's socio-cultural constructive theory, the recommendations were made based on the findings. The implications of the recommendations are that they could improve the equitable and uniform universal allocation of resources ensuring that the quality and access of the programme is standard throughout the country. Also, the researcher proposed some quality assurance guidelines, which would ensure the standardisation of the quality matrix.